1957
DOI: 10.2134/agronj1957.00021962004900010008x
|View full text |Cite
|
Sign up to set email alerts
|

Some Effects of Light Intensity, Temperature, and Soil Moisture on the Growth of Alfalfa, Red Clover and Birdsfoot Trefoil Seedlings1

Abstract: Synopsis The growth response from increased light on alfalfa, red clover and birdsfoot trefoil seedlings in growth chambers was curvilinear for tops and linear for roots. Root growth was affected more than top growth by reduced light intensity. Increasing temperatures from 60° to 90° F. reduced seedling growth. Decreasing soil moisture reduced seedling growth correspondingly. Red clover was affected less by reduced light than alfalfa and birdsfoot trefoil. There was less growth of birdsfoot trefoil than the ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
40
1

Year Published

1958
1958
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 13 publications
2
40
1
Order By: Relevance
“…Ease, equal to RC [34] Slow to establish, weak seedlings [27] Less competitive than RC [35] Vigorous, easy to establish [27] Easy to establish [27] Slow to establish, but persistent [29] Years to establish, then competitive [27] Lifespan/persistence Short-lived perennial, 2-4 years [31] 3-20 years [27] 10+ years [36] Perennial [28] Biennial [27] 1-5 years [27] Perennial [29] 5-20 years [27] Regrowth From crown, high recovery rate [37] From crown [27] From crown [27] Stolons and self-seeding [28] From crown [27] From crown [27] Rhizomes, slow recovery [29] Stolons, slow recovery [27] Competitive capacity High [27] High [27] Moderate [27] Moderate [27] Moderate [27] Persistent and hardy [29] Moderate [27] Drought tolerance Moderate [31] High [27] Moderate [27] Low [36] High [27] Prefers cool, wet conditions [27] Moderate, goes dormant [29] Moderate, goes dormant in drought [27] Shade Red clover germinates in temperatures as low as 5 °C [39] and continues to grow at temperatures above 32 °C, though growth is slowed [40]. It thrives where conditions are shady, cool, and moist [3].…”
Section: Adequacy Of Red Clover For the Proposed Systemmentioning
confidence: 99%
“…Ease, equal to RC [34] Slow to establish, weak seedlings [27] Less competitive than RC [35] Vigorous, easy to establish [27] Easy to establish [27] Slow to establish, but persistent [29] Years to establish, then competitive [27] Lifespan/persistence Short-lived perennial, 2-4 years [31] 3-20 years [27] 10+ years [36] Perennial [28] Biennial [27] 1-5 years [27] Perennial [29] 5-20 years [27] Regrowth From crown, high recovery rate [37] From crown [27] From crown [27] Stolons and self-seeding [28] From crown [27] From crown [27] Rhizomes, slow recovery [29] Stolons, slow recovery [27] Competitive capacity High [27] High [27] Moderate [27] Moderate [27] Moderate [27] Persistent and hardy [29] Moderate [27] Drought tolerance Moderate [31] High [27] Moderate [27] Low [36] High [27] Prefers cool, wet conditions [27] Moderate, goes dormant [29] Moderate, goes dormant in drought [27] Shade Red clover germinates in temperatures as low as 5 °C [39] and continues to grow at temperatures above 32 °C, though growth is slowed [40]. It thrives where conditions are shady, cool, and moist [3].…”
Section: Adequacy Of Red Clover For the Proposed Systemmentioning
confidence: 99%
“…Its influence on plants development and seed germination has been reported in the literature (Coffman, 1923;Gist & Mott, 1957;Dubetz et al, 1962;Allmaras et al, 1964;Smith, 1968).…”
Section: Introductionmentioning
confidence: 98%
“…In similar tests, however, alfalfa root segments took up (4,5,6,7) and Barber et al (1,2,14) reported that excision of the cotyledons from very young seedlings of certain varieties has significant effects on the number of nodes preceding the first flower.…”
mentioning
confidence: 93%
“…Explanations for this growth reduction of the legume include competition for light (5,6), soil moisture (11,15), nutrients (1,4,7,9,10,13), excretion of toxic materials (2,12,14), and effects of the microflora (12).…”
mentioning
confidence: 99%